Synthesis of novel hybrid pharmacophore of N‐((4‐sulfamoylphenyl)carbamothioyl)alkanamides as potent carbonic anhydrase‐II and 15‐lipoxygenase inhibitors. Issue 3 (12th December 2021) - Saeed, Aamer; Khan, Shafi Ullah; Saeed, Maria; Shabir, Ghulam; Hasan, Abbas; Khera, Rasheed Ahmad; El‐Seedi, Hesham; Halim, Sobia Ahsan; Khan, Ajmal; Al‐Harrasi, Ahmed; Iqbal, Jamshed
Abstract: A series of N ‐((4‐sulfamoylphenyl)carbamothioyl)alkanamides (5a‐j) were synthesized by the reaction of sulphanilamide in dry acetone with freshly prepared alkyl and acyl isothiocyanates (5a‐j) . The structures of products were confirmed by IR, 1 H, and 13 C NMR. The synthesized compounds were screened as inhibitors of the bovine erythrocyte carbonic anhydrase isoform II (bCA II) and 15‐lipoxygenase enzyme (15‐LOX). Most of the derivatives showed significant activity against bCA‐II while only few compounds were found active against 15‐LOX. Molecular docking studies of most active compounds were carried out against bCA II as well as 15‐LOX to rationalize the binding mode and interactions of compound in the active sites. Additionally, the pharmacokinetic properties of the compounds were predicted through computational tools, which reflect that these compounds possess acceptable pharmacokinetic profile and good drug‐likeness.